(untitled) (Journal of Informatics Education and Research, 2023)
Augmented reality (AR) is a rapidly growing technology that has the potential to enhance learning outcomes in science education. This paper reviews the existing literature on the role of AR in science education and its effectiveness in enhancing learning outcomes. The findings suggest that AR can improve students’ conceptual understanding, engagement, and motivation, and can help to bridge the gap between abstract concepts and real-world phenomena. However, there are also challenges and limitations associated with the use of AR in science education, such as the need for appropriate hardware and software, the availability of appropriate content, and the need for training for both students and teachers.